Biogeographic shell shape variation in trophon Geversianus (gastropoda: muricidae) along the Southwestern Atlantic coast - Malvé, Mariano Ezequiel (2018)
Broad-scale latitudinal morphological trends in gastropods along the southwestern Atlantic coast are scant, since the majority of studies have focused on local scales. Here, we evaluate biogeographic shell shape variation in the marine gastropod Trophon geversianus across most of its distributional range, covering 14 degrees of latitude. Samples come from death assemblages which have the potential to unveil biogeographic patterns along spatio-temporal scales and are not affected by short-term volatility in comparison with living assemblages. We performed morphometric analyses on shells from death assemblages, and compared shape variation between mid-Holocene and modern shells from one southern site. Multivariate analyses identified two morphotypes matching the biogeographic regions of the Argentine Sea that segregates a warm-temperate from a cold-temperate zone. The Magellan province morphotype is characterized by a larger shell, lower spire height, and higher aperture length than the Argentinean province morphotype. This change in shell shape is significantly correlated to sea surface temperature, even after accounting for spatial autocorrelation, which could be indirectly influencing intraspecific morphoclines via shifts in growth rates. On the other side, shell size and shape variations were also detected (size increase over recent geological time) between mid-Holocene and modern specimens at the Beagle Channel, which could be attributed to paleoenvironmental changes and to shifts in predator-prey relationships. Our study illustrates the usefulness of death assemblages for revealing large-scale patterns of shell-shape variability in mollusk species, and highlights the spatial coincidence of intraspecific morphological differentiation with the transition zone between biogeographic provinces of the Argentine Sea.